Study of the Performance of Speech Recognition Algorithms and Improving the Efficiency of Less-recognition Algorithms - حمود سرار (Latakia University Journal -Engineering Sciences Series, 2021)
In this research I compare performance of famous algorithms of feature extraction in speech recognition MFCC,BFCC,LPCC and PLP, and improving the performance of less recognition algorithms by combination of them to get better time and recognition, despite of the diversity of these methods. Four systems were used for speech recognition, they differ in the used methods during features extraction, the first system used MFCC algorithm, the second system used LPCC algorithm, the third system used BFCC algorithm,and the fourth system used PLP algorithm .The systems used HMM as classifier.I compare results to improvement performance of less recognition algorithms by the combination algorithm. The results were satisfactory in accordance to the improvement level, the effect of increasing the features number on recognition results were studied .